The Nexus between Education and Internet Use of Students: Evidence from Underdeveloped Regions in Indonesia - Purwa, Taly; Cendekia, Diyang Gita (UIII Press, 2022)
During the COVID-19 pandemic and the Industry 4.0 era, the role of the Internet became extremely important for connecting the society. Unfortunately, heterogeneous geographical, socioeconomic and demographic characteristics may create different roles in using the Internet, leading to a digital divide. Utilizing National Socioeconomic Survey (Susenas) data collected early in the COVID-19 pandemic, this study employs binary logistic regression to investigate the effect of education through school participation on internet use in underdeveloped regions in Indonesia. The findings show that only one-fifth of students in underdeveloped regions are using the Internet. Looking deeper, school participation plays a prominent role for students online. The more educated the students, the more likely they are to use the Internet. Moreover, the possibility of a student using the Internet is increasing for students are getting the aid of the Program Indonesia Pintar (PIP), who live in households where the head of the household has particular characteristics, which are being female, of non-productive age, having higher education, working in the non-agricultural sector, having higher socioeconomic status and where fewer students live in the household. However, this study also finds that student gender has no significant impact on internet use. Promoting and providing proportional support by the government in terms of internet use based on school participation is principal due to the existence of the digital divide. It will also be very interesting when further research may account for other potential variables from the supply side that could explain the internet use of students in underdeveloped regions of Indonesia.